Frequent failures in the English language in the secondary school: writing skills - Vera Mero, Selena Jamileth; Tuárez Delgado, Josselyn Nicole; Villafuerte-Holguín, Jhonny (Technium Education and Humanities, 2025)
This study analyzes the frequent writing failures faced by secondary school students in Manabí, Ecuador, when writing in English as a foreign language. The work adheres to the modern paradigm and the mixed-methods research approach. A survey, a semi-structured interview guide, and a focus group guide were used as data collection instruments. The results identified recurring errors in paragraph organization, spelling errors, punctuation, use of connectives and coherence, vocabulary limitations, and difficulties developing complex ideas. Among the most frequent causes of these writing errors in English are the influence of the native language, low student motivation, and the scarcity of resources in rural areas of the country. To improve writing skills, teachers employ strategies that include feedback, listening comprehension, guided writing, and collaborative work. However, there is a lack of technology in writing instruction. Categorical analysis of the collected evidence is necessary. The study concludes with the need for improved teacher training that not only covers grammar but also implements more comprehensive communication skills.